Knowledge and perception of modern learning approaches in Continuing Medical Education: a cross-sectional study - Lugli, Camilla; Murani, Floriana; Bellini, Claudia; Favazzi, Ughetta Maria; Mazzaccara, Alfonso; Vinceti, Marco; Filippini, Tommaso (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Continuing Medical Education (CME) is essential for enhancing professional performance. Modern CME approaches should prioritize adaptability and engagement through interactive and experiential learning, fostering better knowledge retention, skill application, and innovation to meet evolving healthcare challenges. This study aims to assess knowledge and perceptions of perceived role of engagement and active learning techniques in CME in the Italian population.Methods. We conducted a pilot study with cross-sectional design among graduate and post-graduate students from the University of Modena and Reggio Emilia in 2023, by administering a 17-item questionnaire about knowledge, and perceptions of CME.Results. We included 43 participants (median age 25, 72% females). Role of CME was recognized by 72.1%, and 53.5% were aware of its benefits. Likert responses showed high perceived importance of CME and engagement (mean scores 3.79 and 4.40). Active approaches like simulation (68.3%) and role-playing (65.9%) were familiar, but gamification (36.6%) was far less known.Conclusions. While methods like simulation, role-playing, case-based learning, and problem-based learning were familiar to study participants for their strong evidence of effectiveness, emerging approaches such as gamification and team-based learning were less known. Such approaches require further implementation in educational programs to show their benefits.